Research on Quality Management of Municipal Road and Bridge Engineering under the New Situation - Liu, Yang; Yu, Yuanchun (Journal of Theory and Practice of Management Science, 2023)
With the proposal of the goal of people-centered new urbanization construction at the Fifth Plenary Session of the 18th Central Committee, people are increasingly concerned about the quality and safety of urban construction. Municipal road and bridge engineering is related to the development of cities and specific people's livelihoods, so its quality management should be a top priority in urban development and construction under the new situation. There are still some problems in the quality control of municipal road and bridge engineering at present. This article briefly describes the main content of quality management of municipal road and bridge engineering, analyzes the problems in the construction quality management of municipal road and bridge engineering, and finally proposes corresponding improvement strategies for the relevant management of municipal road and bridge engineering quality, for reference.